2004
DOI: 10.1038/sj.npp.1300446
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Infection and Risk for Schizophrenia: IL-1β, IL-6, and TNFα Inhibit Cortical Neuron Dendrite Development

Abstract: Prenatal exposure to infection increases risk for schizophrenia, and we have hypothesized that inflammatory cytokines, generated in response to maternal infection, alter neuron development and increase risk for schizophrenia. We sought to study the effect of cytokines generated in response to infectionFinterleukin-1b (IL-1b), tumor necrosis factor-a (TNFa), and interleukin-6 (IL-6)Fon the dendritic development of cortical neurons. Primary mixed neuronal cultures were obtained from E18 rats and exposed to 0, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
160
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(176 citation statements)
references
References 110 publications
(106 reference statements)
9
160
0
7
Order By: Relevance
“…38 In addition, the macrophage-specific overexpression of IL-10 also abolished the fetal brain TNF-a response to maternal immunological stimulation. TNF-a is known to have potent neurodevelopmental effects by inhibiting neuronal cell survival 11 and cortical dendrite development 12 and synergistic interactions exist between TNF-a and other proinflammatory cytokines in these processes. 12,39 Elevated fetal brain levels of TNF-a have also been implicated in the emergence of enhanced neuronal apoptosis in postnatal life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 In addition, the macrophage-specific overexpression of IL-10 also abolished the fetal brain TNF-a response to maternal immunological stimulation. TNF-a is known to have potent neurodevelopmental effects by inhibiting neuronal cell survival 11 and cortical dendrite development 12 and synergistic interactions exist between TNF-a and other proinflammatory cytokines in these processes. 12,39 Elevated fetal brain levels of TNF-a have also been implicated in the emergence of enhanced neuronal apoptosis in postnatal life.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is known to have potent neurodevelopmental effects by inhibiting neuronal cell survival 11 and cortical dendrite development 12 and synergistic interactions exist between TNF-a and other proinflammatory cytokines in these processes. 12,39 Elevated fetal brain levels of TNF-a have also been implicated in the emergence of enhanced neuronal apoptosis in postnatal life. 17 Furthermore, increased maternal TNF-a levels during pregnancy have been directly associated with a higher incidence of postpubertal psychosis in the offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The cause of schizophrenia is unknown, but evidence suggests that this condition is associated with alterations in prefrontal connectivity involving glutamate transmission at NMDA receptors. 9 Most attractive is the suggested association between prenatal exposure to infection and the risk for schizophrenia, together with the role of cytokines in reducing dendrite development, 10 consistent with the neuropathology of schizophrenia. 11 Interestingly, we found that early exposure to UCB leads to impairment of neuronal development by reduction in the dendrite extension and ramification 12 and that this can possibly increase the risk for mental illness in later life.…”
Section: Introductionmentioning
confidence: 96%
“…En pacientes esquizofrénicos se han evaluado los niveles de citokinas inflamatorias, encontrán-dose hasta la fecha resultados variables en los distintos estudios, pero en su mayoría muestran aumento de IL2, IL-6, ILß 1 y TNFα 46,47 . La medición de la proteína inflamatoria PCR también se ve elevada en estos pacientes, asociándose los niveles aumentados a mayor gravedad y compromiso psiquiátrico 48 .…”
Section: Fármacounclassified